A Review of the Integration of a Socio Scientific Issues Approach Based on Local Wisdom in Chemistry Education (Context of Local Wisdom in East Java) - Silfianah, Ifah; Adyana, Hendar Dio; Wahyuni, Tutik Sri (Universitas Negeri Malang, 2024)
In learning, the SSI approach involves utilising social science-related topics that engage students in dialogue, discussion, and debate. This SSI approach is pertinent to chemistry education, which connects to real-life situations. Local wisdom-based learning is understood as the process that draws from students' cultural and social environment and is linked to educational materials. This study aims to explore the topic of SSI through the lens of local wisdom in chemistry education. This study comprises a literature review employing a qualitative descriptive analysis method. The findings indicate that integrating SSI and local wisdom merges scientific understanding with the context of social issues pertinent to the environment and local culture. This approach emphasises mastery of scientific concepts regarding social issues and fosters an appreciation of the local wisdom surrounding them. In addition to enhancing critical thinking skills and scientific literacy through SSI, this approach's integration can also heighten awareness and concern for local wisdom. In the context of local wisdom in East Java, three topics may serve as references for promoting SSI-local wisdom in chemistry education, including issues related to sound water quality in Gamping village, a hub for the Tulungagung marble handicraft industry, Malang dairy farms that potentially contribute to greenhouse gas emissions, and culinary shellfish sourced from microplastic-polluted waters in Sidoarjo and Surabaya. These SSI-local wisdom topics in chemistry education can be further developed as contexts in learning resources or incorporated into various chemistry teaching models.